Gaining Access to the Superior Ophthalmic Vein for Endovascular Embolization of Indirect Carotid-Cavernous Fistulas. Issue 4 (June 2021) - Daigle, Patrick; Brenna, Connor Thomas Arthur; da Costa, Leodante; Yang, Victor; Gill, Harmeet Singh
Abstract : Abstract: Carotid-cavernous fistulas (CCFs) are abnormal connections between the carotid arterial system and the cavernous sinus. These acquired vascular malformations may result in severe orbital congestion and sight-threatening complications. The authors present their experience in gaining access to the superior ophthalmic vein to embolize indirect CCFs in three different patients. Surgical exposure and cannulation of the SOV were successful in all 3 cases. One patient developed an orbital compartment syndrome towards the end of the embolization process, after the irrigation cannula was inadvertently dislodged from the SOV. He required a lateral canthotomy and inferior cantholysis but did not suffer from any related sequelae. Signs and symptoms resolved gradually in all patients and cosmetic results were excellent. In our experience, the SOV offers a reliable access to indirect CCFs, but patients should be monitored closely during the embolization process to prevent ophthalmic complications.